Ossification of Cranial Epidural Hematomas: A Systematic Review of Management Strategies and Presentation of an Illustrative Case - Insa K. Janssen; Julien Haemmerli; Andrea Bartoli; Melvin Joory; Emily Richards; Karl Schaller; Aria Nouri (Neurotrauma Reports)
The presence of a calcified or ossified chronic cranial epidural hematoma (EDH) is rare and has been described in only a few case reports in the literature. Consequently, clear treatment strategies remain elusive and may entail conservative and surgical approaches. In this study, we performed a systematic review of reported cases to evaluate the clinical course and treatment options for these patients. A comprehensive systematic search of two databases was performed, and information on patient characteristics, symptomatology, and treatment was extracted from eligible articles. A total of 56 cases were included in our analyses. Forty patients were male, 16 were female, with an average age of 21.38 years at the time of diagnosis. Assumed etiology was previous trauma in 35 cases, previous cranial surgery in 17 patients, and birth trauma and epidural bleeding after the utilization of the Mayfield clamp in 1 case each. The origin remained unclear in two cases. The time between trauma or surgery and diagnostics ranged between one and a half weeks and 50 years, with a median of 4 years (SD 9.8 years). The symptoms were very heterogeneous, ranging from acute neurological deterioration to chronic symptoms. In 15 cases, patients were asymptomatic, and cranial imaging was performed as part of a new trauma or a screening for other disease. Forty-one patients received surgical treatment by craniotomy and hematoma evacuation, and 13 patients were treated conservatively. In two cases, the liquid hematoma portion was aspirated through a burr hole. The localization of calcified or ossified EDH was mainly supratentorial. Young male patients most commonly present with calcified or ossified EDH after trauma, according to the epidemiological trend of acute EDH. Clinical presentation varies from asymptomatic to severe neurological deficits and signs of increased intracranial pressure. There is no standardized treatment; decisions must be made on an individual basis.